Efficiency of Sophora flavescens-Fructus Ligustri Lucidi Drug Pairs in the Treatment of Liver Fibrosis Based on the Response Surface Method. (1st April 2019) - Chu, Shuhan; Zhang, Hongxu; Ding, Lixin
Abstract : The pairing of Sophora flavescens and Fructus Ligustri lucidi is taken from Shi Jinmo Medicine. The idea behind this pairing was inspired by the similarity in pharmacological effects of the two herbal drugs, both of which are known to be effective in the treatment and protection against liver fibrosis. To quantitatively study the extent of the interaction between these drugs and the effect of pairing on the treatment of liver fibrosis, an animal model of liver fibrosis mice was established by intraperitoneal injection of low-dose carbon tetrachloride. The drugs were then administered individually, or in predefined compatibility ratio pairs, by gavage, and the effects on indexes of liver fibrosis were observed. The multisynthetic index method was adopted using Matlab software in order to construct a three-dimensional response surface map of the integration effect and conduct interaction analysis of Sophora flavescens and Fructus Ligustri lucidi. The quadratic surface fitting pattern was designed by quadratic regression to determine the optimal range of each drug. The obtained results show that when the compatibility ratio of Sophora flavescens -Fructus Ligustri lucidi drug pairs is less than or equal to 1:1, their therapeutic effect is enhanced by synergy (interaction value ranging between -0.2 and -1). Overall, the synergy of the high-dose drug pairs is stronger than that of the low-dose drug pairs. The optimal dose ranges are 6~12 g and 8~17 g for Sophora flavescens and Fructus Ligustri lucidi, respectively.